Tracing non-fungal eukaryotic diversity via shotgun metagenomes in the complex mudflat intertidal zones - He Han; Mengzhi Ji; Yan Li; Xiaofan Gong; Wen Song; Jiayin Zhou; Kai Ma; Yuqi Zhou; Xia Liu; Mengqi Wang; Yueyue Li; Qichao Tu (mSystems)
ABSTRACT Eukaryotes, both micro- and macro-, constitute the dominant component of Earth’s biosphere visible to the naked eye. Although relatively big in organismal size, tracing eukaryotic diversity in complex environments is not easy. For example, they may actively escape from sampling and be physically absent from the collected samples. In this study, we strived to recover non-fungal eukaryotic DNA sequences from typical shotgun metagenomes in the complex mudflat intertidal zones. Multiple recently developed approaches for identifying eukaryotic sequences from shotgun metagenomes were comparatively assessed. Considering the low overlap among different approaches, an integrative workflow was proposed. The integrative workflow was then used to recover the eukaryotic communities in complex intertidal sediments. The temporal dynamics of intertidal eukaryotic communities were investigated through a time-series sampling effort. Thirty-four non-fungal eukaryotic phyla were detected from 36 shotgun metagenomes. Clear temporal variation in relative abundance was observed for eukaryotic genera such as Timema and Navicula. Strong temporal turnover of intertidal eukaryotic communities was observed. By comparing to 18S rRNA gene amplicon sequencing, dramatically different community profiles were observed between these two approaches. However, the temporal patterns for intertidal eukaryotic communities recovered by both approaches were generally comparable. This study provides valuable technical insights into the recovery of non-fungal eukaryotic information from complex environments and demonstrates an alternative route for reusing the massive metagenomic data sets generated in the past and future.IMPORTANCEEukaryotes represent the dominant component visible to the naked eye and contribute to the primary biomass in the Earth’s biosphere. Yet, tracing the eukaryotic diversity in complex environments remains difficult, as they can actively move around and escape from sampling. Here, using the intertidal sediments as an example, we strived to retrieve non-fungal eukaryotic sequences from typical shotgun metagenomes. Compared to 18S rRNA gene amplicon sequencing, the shotgun metagenome-based approach resolved dramatically different eukaryotic community profiles, though comparable ecological patterns could be observed. This study paves an alternative way for utilizing shotgun metagenomic data to recover non-fungal eukaryotic information in complex environments, demonstrating significant potential for environmental monitoring and biodiversity investigations.